Circulating Syndecan-1 and Tissue Factor Pathway Inhibitor, Biomarkers of Endothelial Dysfunction, Predict Mortality in Burn Patients. Issue 2 (August 2021) - Keyloun, John W.; Le, Tuan D.; Pusateri, Anthony E.; Ball, Robert L.; Carney, Bonnie C.; Orfeo, Thomas; Brummel-Ziedins, Kathleen E.; Bravo, Maria C.; McLawhorn, Melissa M.; Moffatt, Lauren T.; Shupp, Jeffrey W.
ABSTRACT: Objective: The aim of this study is to evaluate the association between burn injury and admission plasma levels of Syndecan-1 (SDC-1) and Tissue Factor Pathway Inhibitor (TFPI), and their ability to predict 30-day mortality. Background: SDC-1 and TFPI are expressed by vascular endothelium and shed into the plasma as biomarkers of endothelial damage. Admission plasma biomarker levels have been associated with morbidity and mortality in trauma patients, but this has not been well characterized in burn patients. Methods: This cohort study enrolled burn patients admitted to a regional burn center between 2013 and 2017. Blood samples were collected within 4 h of admission and plasma SDC-1 and TFPI were quantified by ELISA. Demographics and injury characteristics were collected prospectively. The primary outcome was 30-day in-hospital mortality. Results: Of 158 patients, 74 met inclusion criteria. Most patients were male with median age of 41.5 years and burn TBSA of 20.5%. The overall mortality rate was 20.3%. Admission SDC-1 and TFPI were significantly higher among deceased patients. Plasma SDC-1 >34 ng/mL was associated with a 32-times higher likelihood of mortality [OR: 32.65 (95% CI, 2.67–399.78); P = 0.006] and a strong predictor of mortality (area under the ROC [AUROC] 0.92). TFPI was associated with a nine-times higher likelihood of mortality [OR: 9.59 (95% CI, 1.02–89.75); P = 0.002] and a fair predictor of mortality (AUROC 0.68). Conclusions: SDC-1 and TFPI are associated with a higher risk of 30-day mortality. We propose the measurement of SDC-1 on admission to identify burn patients at high risk of mortality. However, further investigation with a larger sample size is warranted.